Antimicrobial Effects of Quercusinfectoria, MatricariachmomillaExtracts, and AlumAgainst Bacteria Isolated from Woman with Sever Vaginitis - Nada KhazalKadhim Hindi; Lubna Abdul Muttalib Al-shalah; Zainab Adil Ghani Chabuck (Al-Qadisiyah Journal of Pure Science, 2018)
Plant extractis considered as natural, safe, accessible and inexpensive materials has been grown for the treatment of bacterial infections. This workwas carried out to decidethe inhibitory activities of Quercusinfectoria, Matricariachmomillaand Alumon bacterial vaginitis and vaginal yeast infections.In vitro antimicrobial activity of Quercusinfectoria,Matricariachmomillaand chemical material Alumwere studied against Staphylococcus aureus, streptococcus agalactiae, Enterobacter spp., E. coli,. andcandida albicana. The inhibitory effects of extracts were compared with standard antibiotic ciprofloxacin.The mean of inhibition zonesthatobtained from these extracts were range from (20-35mm).This study illustrates that the aquatic extracts of these materials can beused as a potential source of unusual antimicrobial agents used for bacterialvaginosis and vaginal yeast infection.Also, bacterial infections werethe highest responsive to plant extracts rather than yeast infection, especiallly Strep agalactiae.